Marital therapy in mainland China: a qualitative study of young adults’ knowledge, attitudes, and beliefs - Anderson, Jared R.; Aducci, C. J.; Adams, Rebekah D.; Johnson, Matthew D.; Liu, Wenli; Zheng, Fuming; Ratcliffe, G. Cole (My University, 2013)
This qualitative study explored young adults' knowledge, attitudes, and beliefs about marital therapy in Mainland China. Participants (N = 24) were undergraduate and graduate students attending university in Beijing and Guangzhou. Four themes emerged from the data analysis: (1) beliefs regarding marital therapy, (2) role of the therapist, (3) barriers to seeking marital therapy, and (4) greater accessibility to marital therapy. In general, our participants knew little about marital therapy and were concerned that using such services could bring shame to them or to their family and that the cost of such services would be beyond most citizens' means. In addition, participants believed that marital therapists would serve as experts doling out relationship advice, whereas clients would generally take a passive role. Increased government support, alternative forms of treatment that included phone and web-based services as a way to protect anonymity and therefore confidentiality, and government credentialing were seen as steps that could increase the use and accessibility of marital therapy in Mainland China.
Keywords: Mainland China; Marital therapy; Young adults; Barriers to service